2015
DOI: 10.1111/rda.12646
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein‐6 (BMP‐6) Stimulates the Antrum Formation by the Regulation of its Signalling Pathway in Caprine Pre‐antral Follicles Cultured In Vitro

Abstract: BMP-6 has been found to be important to ovarian cells and oocyte, as well as to uterus. Thus, this study investigated the effect of bone morphogenetic protein (BMP-6) and recombinant follicle-stimulating hormone (rFSH) alone or in combination on the in vitro culture (IVC) of isolated caprine secondary follicles (Experiment 1) and the mRNA levels for BMP receptors/Smad signalling pathway (BMPR1A, BMPR2, SMAD1, SMAD4, SMAD5, SMAD6, SMAD7 and SMAD8) in vivo and in vitro using BMP-6 (Experiment 2). Secondary folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Conversely, mutations in the BMP-15 gene are associated with infertility in sheep and premature ovarian failure in humans (32,33). Other studies have demonstrated that BMP-6 is associated with follicle growth in the pre-antral and antral stages (34,35). In addition, some studies have demonstrated that BMP-15 and GDF-9 are able to stimulate granulosa cell mitosis in pre-antral follicles (12,31,36).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mutations in the BMP-15 gene are associated with infertility in sheep and premature ovarian failure in humans (32,33). Other studies have demonstrated that BMP-6 is associated with follicle growth in the pre-antral and antral stages (34,35). In addition, some studies have demonstrated that BMP-15 and GDF-9 are able to stimulate granulosa cell mitosis in pre-antral follicles (12,31,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies on iFFA are lagged behind. For example, the latest review on iFFA was published in 2010 ( 18 ), and only handful research articles on iFFA could be retrieved from the PubMed database ( 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ). In addition, the research targets are relative narrow.…”
mentioning
confidence: 99%